Methane gas flares in the forearc basin of the Andaman-Nicobar subduction zone - Ankush,; Dewangan, P.; Sriram, G. (Frontiers in Earth Science, 2024)
Gas hydrates deposits in the Andaman forearc basin are inferred from seismic data and confirmed by drilling/coring during the NGHP-01 expedition. We present new evidence of gas flares in the Andaman forearc basin, detected through water column imaging (WCI), subbottom profiling, and high-resolution seismic data acquired onboard RV Sindhu Sadhana (SSD-085) in November-December 2021. The gas flares are located over an elongated sedimentary ridge, featuring two prominent mounds (M1 and M2) with distinct geological features. Compressional tectonics induced by the Diligent fault (DLF) formed the ridge with varying slopes and elevations. Gas flares observed above the mound M1 in WCI and sub-bottom profiler data. Seafloor samples reveal carbonate rocks with visible pores, indicating gas/fluid migration or burrows. The regional seismic profile delineates three sedimentary sequences: folded and faulted strata, mass transport deposits, and horizontal-to-sub-horizontal sedimentary layers. Additionally, we observed a bottom simulating reflector (BSR), indicating potential subsurface gas hydrate deposits. Detailed high-resolution seismic data revealed complex fault systems near bathymetry mounds (M1 and M2), which may serve as pathways for vertical fluid/gas migration.